Ημι-Μαρκοβιανές διαδικασίες και θεωρία αξιοπιστίας: θεωρητικές προσεγγίσεις μετ' εφαρμογών - Κρουστάλλη, Χρυσούλα (2022)
In Reliability Analysis the main focus is on stochastic processes and in particular semi-Markov processes since they allow for general lifetime distributions. In this thesis, we introduce a family of lifetime distributions, the H-class of distributions, which is closed under minimum. However, some distributions, that we are interested in, do not belong to the H-class, like the Modified Weibull Poisson distribution and therefore we approximate them, by members of the H-class. Moreover, using the multi-state systems and semi- Markov methodology, we produce maximum likelihood estimators for the parameters of the distribution of H-class.